Preliminary Evaluation of the Values Tracker: A Two-Item Measure of Engagement in Valued Activities in Those With Chronic Pain. (January 2016) - Pielech, Melissa; Bailey, Robert W.; McEntee, Mindy L.; Ashworth, Julie; Levell, Jayne; Sowden, Gail; Vowles, Kevin E.
Engagement in valued activities is an important outcome, particularly in treatments that aim to enhance quality of life in those with chronic conditions. The present study describes the initial evaluation of the Values Tracker (VT), a two-item measure of values engagement, in 302 treatment-seeking adults with chronic pain. Hierarchical regression analyses were conducted to examine the utility of the VT in the statistical prediction of pain-related functioning, after controlling for demographic variables, pain intensity, and pain-related distress. Across analyses, pain intensity accounted for significant variance (range Δ R 2 = .06-.09) with pain-related distress adding additional unique variance (range Δ R 2 = .07-.19). The VT accounted for additional unique variance (range Δ R 2 = .02-.17) for all variables with the exception of physical disability. These findings provide initial support for the utility of the VT in those with chronic pain. Given the VT's brevity, it may be particularly useful for tracking changes in engagement in values across sessions.